The Question of Pideia of Subjectivity - Masoud Omid (Journal of Philosophical Investigations, 2022)
The foundation of our world is based on subjectivity. In such a world and from the perspective of subjectivity, although a person is not born a subject, he becomes a subject. But reaching the level of subjectivity is the responsibility of subjectivity and its educational horizon and discourse; It is in this way that a person learns subjectivity and subjectivity comes. With this description, this article seeks to raise a question and then a research about subjectivity under the title of subjectivity paidia. This question is a topic that can be raised and discussed due to the wide and deep relationship of subjectivity with the history of philosophy and the modernity period, as well as its relationship with our contemporary way of thinking and life. Paideia of subjectivity, as a current with Greek, Renaissance and modern contexts, is first of all concerned with education, and secondly, it is a platform for practicing subjectivity in terms of opinion and action, and finally, it is aimed at cultivating something called the subject. The paidia of subjectivity is not aimed at the education of human beings in a neutral and unconditional way, but it is an education of a subjective type, subject-type or subject-oriented about humans. Paideia of subjectivity, in the sense of subjectivity education and subjectivity training and subject education, has historical roots and its contexts and footprints can be more or less and in different ways, in Greece and the periods after that and up to the period Contemporary sat watching. Questioning the paidia of subjectivity, from a descriptive point of view, can help us discover the characteristics and components of this current, and on the other hand, from a prescriptive and recommendatory point of view, it can reveal the elements and general educational directions of this current, paidia of subjectivity, can be discussed as a foundation for all philosophies of education.